Reading Wiredu - Hallen, B. (World philosophies., 2021)
"Reading Wiredu is the first comprehensive overview of the philosophical thought of Kwasi Wiredu. Born in Ghana in 1931, Wiredu, an important observer and critic of philosophy generally, remains an original and penetrating African thinker. Interrelating Wiredu's philosophical writings from across decades, Barry Hallen sets forth the basic tenets and the defining features of his philosophy. Wiredu's thought is divided into five distinct but interconnected areas: his response to the philosophy of Quine on issues of logic and ontology, issues of language in philosophical reflection, the nature of truth as a practical and philosophical concern, the principle of sympathetic impartiality that all human beings must live by to survive as a group, and finally, consensus building as rooted in intentional, negotiated, and rational exchanges that are part of everyday life. Reading Wiredu explores the scope and depth of Wiredu's philosophical thought, which can be framed through what he calls a genetic methodology-a methodology that privileges environmental considerations in the production of various forms of thought. Hallen's overview is intended to assist scholars and students in grasping Wiredu's complex philosophical thought"--